2019
DOI: 10.1038/s41598-019-46513-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between childbirth, breastfeeding, and uterine fibroids: an observational study

Abstract: The aim of this study was to investigate the effect of childbirth and breastfeeding on uterine fibroids and to identify the factors associated with size variations. This was a monocenter observational study carried on women with a sonographic diagnosis of uterine fibroids from January 2007 to December 2016, with no indication for immediate treatment, and who became pregnant within one year from diagnosis. All patients were re-evaluated six months after delivery. Fibroid diameters were compared between pre-preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
(47 reference statements)
0
6
0
1
Order By: Relevance
“…The consequences of marriage between these individuals are the same as consanguineous marriage and put children born of such marriage at risk for certain disorders [ 10 , 12 ]. Moreover, breastfeeding has many benefits for the physical and emotional health of breastfeeding mothers [ 13 ], such as improving uterine involution, reducing bleeding, preventing anemia [ 14 , 15 ], reducing the risk of postpartum depression by regulating cortisol circadian rhythms [ 16 , 17 ], decreasing the risk of type 2 diabetes (T2D), cardiovascular diseases, and metabolic syndrome, and protecting against breast cancer (BC) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of marriage between these individuals are the same as consanguineous marriage and put children born of such marriage at risk for certain disorders [ 10 , 12 ]. Moreover, breastfeeding has many benefits for the physical and emotional health of breastfeeding mothers [ 13 ], such as improving uterine involution, reducing bleeding, preventing anemia [ 14 , 15 ], reducing the risk of postpartum depression by regulating cortisol circadian rhythms [ 16 , 17 ], decreasing the risk of type 2 diabetes (T2D), cardiovascular diseases, and metabolic syndrome, and protecting against breast cancer (BC) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Delli Carpini et al [14] observed a significant increase in myoma size in early pregnancy, as compared to the size prior to pregnancy, unchanged myoma size during the second half of the pregnancy, and a significant decrease in myoma size after delivery.…”
Section: Biological Behavior Of Myomas During Pregnancymentioning
confidence: 84%
“…Deli Karpini i saradnici [14] su u svom istraživanju uočili značajan porast veličine mioma u ranoj trudnoći u odnosu na veličinu pre trudnoće, nepromenjenu veličinu mioma tokom druge polovine trudnoće i značajno smanjenje veličine mioma nakon porođaja.…”
Section: Mechanisms Of the Development Of Perinatal Complicationsunclassified
“…However, due to the increased hormones during pregnancy, many pregnant women tend to experience large growth of their fibroids. Importantly, after giving birth, 70% of postpartum women experience shrinkage of their fibroids ( Laughlin et al, 2011 ; Guo and Segars, 2012 ; Delli Carpini et al, 2019 ). This shrinkage is hypothesized to be caused by uterine ischemia when the placenta is torn from the uterine wall, causing immense blood loss.…”
Section: Locationmentioning
confidence: 99%